Fluorescent temperature measurement material with high sensitivity and preparation method thereof
By preparing a fluorescent thermometric material with an A4B2M1-xO6F:xMn4+ structure, the problems of low temperature sensitivity and high production cost were solved, and high-sensitivity temperature measurement and stable fluorescent thermometric effect were achieved.
Patent Information
- Application Number
- CN202511519309.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2026-01-09
AI Technical Summary
Existing fluorescent thermometric materials have low temperature sensitivity and a narrow excitation wavelength range, which leads to high requirements for lasers. The change in emission peak/excitation wavelength with temperature affects the measurement stability, and the production cost is high.
A fluorescent thermometric material with an A4B2M1-xO6F:xMn4+ structure is used, where A is Na, Li, or K, B is Mg, Zn, or Ca, and M is Nb or Sb. The Mn4+ doping amount is 0.05 mol% ≤ x ≤ 1 mol%. It emits red light in the range of 600-850 nm when excited by near-ultraviolet or visible light. The preparation method includes mixing, pre-firing, sintering, and grinding steps.
High-sensitivity temperature measurement has been achieved. The luminescent thermometric material has a temperature measurement accuracy of 9.65%/K in the range of 304K to 460K. The preparation process is simple, low-cost, environmentally friendly, and chemically stable.
Smart Images

Figure CN121293981A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of fluorescent temperature measurement materials, and particularly relates to a fluorescent temperature measurement material with high sensitivity and a preparation method thereof. BACKGROUND
[0002] Temperature is a parameter that is often measured in many applications, including biosensing, environmental monitoring, medicine and diagnostics. Unlike traditional thermometers, non-contact optical thermometers have unique advantages such as fast response speed, non-invasive operation, spatial resolution and temperature resolution, which are beneficial to work or detect fast-moving objects in harsh environments such as medical, high-temperature, electromagnetic, thermal and corrosive environments, which makes the non-contact temperature measurement technology based on fluorescent materials receive widespread attention. The core of the fluorescent temperature measurement technology is to establish the correspondence between the optical properties of the optical material and the temperature, which can be used to measure the temperature change of the surface of the material model in real time and dynamically by monitoring the change of the luminescent properties of the material after the material is attached to the surface of the measured model in the form of a coating. The temperature-sensitive optical properties of the fluorescent material usually include emission peak width, fluorescence intensity ratio, fluorescence lifetime, absolute intensity and long afterglow time. As the core working substance of this technology, the temperature-sensitive luminescent material should generally have high light conversion efficiency, sensitive temperature response and fast luminescent decay speed. However, the most commonly used luminescent ion for optical temperature sensing fluorescent powder is rare earth ions, because rare earth ions have special advantages such as being insensitive to excitation power fluctuations and being insensitive to the movement of luminescent particles in the matrix. However, the 4f energy level emission of trivalent rare earth ions is a sharp peak, which requires precise measuring instruments to record the accurate curve of the emission peak, which will increase the cost of the optical temperature measurement instrument. In addition, the shift of the emission peak or excitation wavelength with temperature change can also destroy the stability of the measurement. On the other hand, divalent rare earth ions with broadband excitation / emission spectrum have low chemical stability, which is difficult to meet the practical application requirements in the temperature sensing field. Therefore, it is of great significance to find fluorescent powder with higher temperature sensitivity, stable chemical valence and higher measurement stability. Compared with the luminescence of rare earth ions in temperature-sensitive luminescent materials, the broadband emission of Mn 4+ ions has the advantages of better anti-peak shift capability and lower requirement for measuring instruments, and it is also easier to select the excitation wavelength for broadband ultraviolet or visible light excitation, thereby reducing the requirement for lasers.
[0003] Double perovskite red Ba2LaTaO6:Mn 4+ The fluorescent temperature measurement material provided by the fluorescent powder takes a compound with cubic double perovskite as a matrix, and Mn 4+ ions as a luminescent center, which has stable chemical valence and is easy to synthesize. The luminescent temperature measurement material can be effectively excited by near-ultraviolet or visible light, and emits bright red light in the range of 600-750 nm, and the emission peak or excitation wavelength moves relatively small with temperature change.
[0004] The existing fluorescent powder temperature measuring material has low temperature sensitivity, narrow excitation wavelength range, high requirement for laser, high production cost due to the need of precise measuring instrument to record the accurate curve of the emission peak, and the emission peak / excitation wavelength moves with the change of temperature, which affects the measurement stability. Therefore, a preparation method of a fluorescent temperature measuring material with high sensitivity is needed. SUMMARY
[0005] The purpose of the present application is to provide a fluorescent temperature measuring material with high sensitivity to solve the problems existing in the prior art.
[0006] To achieve the above purpose, the present application is implemented according to the following technical solutions:
[0007] On the one hand, the fluorescent temperature measuring material has the following general formula: A4B2M 1-x O6F:xMn 4+ ,
[0008] Among them, A metal is one or more of elements Na, Li and K; B metal is one or more of Mg, Zn and Ca; M metal is one or both of elements Nb and Sb; the doping amount x of Mn 4+ is in the range of 0.05mol%≤x≤1mol%.
[0009] Further, the fluorescent temperature measuring material has a face-centered cubic rock salt structure, can be excited by near ultraviolet or visible light of 300-600nm, and emits red light in the range of 600-850nm.
[0010] On the other hand, a preparation method of a fluorescent temperature measuring material with high sensitivity is used to prepare the fluorescent temperature measuring material with high sensitivity, which comprises the following steps:
[0011] (1) Mix manganese source, A metal source, B metal source and M metal source, and grind once to obtain a raw material mixture; wherein the A metal source is a combination of fluoride corresponding to A metal and carbonate corresponding to A metal, and the molar ratio of fluoride corresponding to A metal to carbonate corresponding to A metal is 1:1.5; or any one of a combination of fluoride corresponding to A metal and nitrate corresponding to A metal, a combination of fluoride corresponding to A metal and acetate corresponding to A metal, and the molar ratio of fluoride corresponding to A metal to nitrate corresponding to A metal is 1:3, and the molar ratio of fluoride corresponding to A metal to acetate corresponding to A metal is 1:3;
[0012] The molar ratio of B metal source to fluoride in A metal source is 2:1;
[0013] The molar ratio of the M metal source to the manganese source is (0.99-0.9995):(0.0005-0.01);
[0014] (2) The raw material mixture is pre-fired at 200-800°C for 0.5-24 hours, and after cooling at room temperature, the mixture is secondly ground to obtain a pre-fired mixture;
[0015] (3) The pre-fired mixture is sintered at 800-1100°C for 3-24 hours, and after cooling, the sample is taken out and thirdly ground to obtain the fluorescent temperature measuring material.
[0016] Further, the manganese source includes any one or combination of manganese-containing oxides, carbonates, halides, oxalates, acetates or nitrates; the A metal-containing source includes any one or combination of A element-containing oxides, halides, carbonates, nitrates, oxalates, citrates or acetates; the B metal-containing source includes any one or combination of B element-containing oxides, halides, carbonates, oxalates, citrates, acetates or nitrates; and the M metal-containing source includes any one or combination of M element-containing oxides, carbonates, nitrates, oxalates, citrates or acetates.
[0017] Further, when the A metal is Li, the A metal source is a combination of LiF and Li2CO3, LiF and LiNO3 or LiF and CH3COOLi; when the A metal is Na, the A metal source is a combination of NaF and Na2CO3; and when the A metal is K, the A metal source is a combination of KF and K2CO3.
[0018] Further, when the B metal is Mg, the B metal source is MgO, Mg(NO3)2 or Mg(CH3COO)2; when the B metal is Zn, the B metal source is ZnO; and when the B metal is Ca, the B metal source is CaCO3.
[0019] Further, when the M metal is Nb, the M metal source is Nb2O5, Nb(NO3)5 or Nb(CH3COO)5; when the M metal is Sb, the M metal source is Sb2O5; when the M metal is Ta, the M metal source is Ta2O5; when the M metal is P, the M metal source is P2O5; when the M metal is V, the M metal source is V2O5; and when the M metal is Ta, P or V, the molar ratio of the M metal source to Nb2O5 is (0.005-0.25):(0.4995-0.25).
[0020] Further, the time for the first, second and third grinding is 5-120 minutes.
[0021] The present application has the following beneficial effects:
[0022] The present application is a fluorescent temperature measurement material with high sensitivity, which has the following technical effects compared with the prior art:
[0023] The luminescent temperature measurement material of the present application can be effectively excited by near-ultraviolet or visible light, has high color purity, good luminescence detectability, and a temperature measurement accuracy of 9.65% / K in the range of 304K to 460K; at the same time, the luminescent temperature measurement material has simple preparation process, low raw material and equipment cost, environmental friendliness, stable product chemical properties, and is suitable for general use. BRIEF DESCRIPTION OF DRAWINGS
[0024] Figure 1 is the X-ray diffraction spectrum (XRD) of the luminescent temperature measurement material prepared in Example 1 of the present application.
[0025] Figure 2 is the excitation and emission spectrum of the luminescent temperature measurement material prepared in Example 1 of the present application at room temperature.
[0026] Figure 3 is the emission spectrum of the temperature measurement material prepared in Example 1 of the present application at different temperatures.
[0027] Figure 4 is the temperature response curve of the luminescent temperature measurement material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0028] The present application will be further described below through specific examples, and the illustrative examples of the present application and the description are used to explain the present application, but do not limit the present application.
[0029] Example 1
[0030] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%) and MnO2 (99.99%), and the molar ratio between them is 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 30 minutes before being placed in an alumina crucible. The pre-sintering is carried out at 650°C for 6 hours. The pre-sintered sample is taken out, ground again, mixed uniformly, and placed in an alumina crucible for further calcination at 950°C for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain the luminescent temperature measurement fluorescent powder. The obtained luminescent temperature measurement powder is a light red powder, and the molecular formula is 2MgO·Li2O·LiF·LiNb 0.999 Mn 0.001O3, its emission spectrum consists of a broadband emission peak with a peak at 677 nm under the strongest excitation at 340 nm, the emission spectrum covers the range of 600-850 nm, as shown in Figure 2 ; as the temperature rises, the emission peak intensity decreases sharply, as shown in Figure 3 ; the emission peak intensity changes linearly with temperature, as shown in Figure 4 ; the best temperature measurement sensitivity of the material in the range of 304K to 460K is 9.65% / K.
[0031] Example 2
[0032] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%) and MnO2 (99.99%), and the molar ratio between them is 1:1.5:2:0.4975:0.005. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar and ground for about 30 minutes, then placed in an alumina crucible, and pre-fired at 650°C for 6 hours. The pre-fired sample is taken out, ground and mixed again, then placed in an alumina crucible, and calcined at 950°C for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain a luminescent thermometric fluorescent powder. The obtained luminescent thermometric powder is a light red powder, and the molecular formula is 2MgO·Li2O·LiF·LiNb 0.995 Mn 0.005 O3, its emission spectrum consists of a broadband emission peak with a peak at 677 nm under the strongest excitation at 340 nm, the emission spectrum covers the range of 600-850 nm, as shown in Figure 2 ; as the temperature rises, the emission peak intensity decreases sharply, as shown in Figure 3 ; the emission peak intensity changes linearly with temperature, as shown in Figure 4 ; the best temperature measurement sensitivity of the material in the range of 304K to 460K is 8.85% / K.
[0033] Example 3
[0034] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%) and MnO2 (99.99%), and the molar ratio between them is 1:1.5:2:0.495:0.01. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar and ground for about 30 minutes, then placed in an alumina crucible, and pre-fired at 650°C for 6 hours. The pre-fired sample is taken out, ground and mixed again, then placed in an alumina crucible, and calcined at 950°C for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain a luminescent thermometric fluorescent powder. The obtained luminescent thermometric powder is a light red powder, and the molecular formula is 2MgO·Li2O·LiF·LiNb 0.99 Mn0.01 O3, its emission spectrum under the strongest excitation at 340 nm consists of a broadband emission peak with a peak at 677 nm, and the emission spectrum covers the range of 600-850 nm, as shown in Figure 2 As the temperature rises, the emission peak intensity decreases sharply, as shown in Figure 3 As the temperature rises, the emission peak intensity decreases sharply, as shown in Figure 4 The optimal temperature measurement sensitivity of the material in the range of 304K to 460K is 7.74% / K.
[0035] Example 4
[0036] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%), and MnO2 (99.99%), and the molar ratio between them is 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 30 minutes, then placed in an alumina crucible, and pre-fired at 650°C for 0.5 hours. The pre-fired sample is taken out, ground and mixed again, then placed in an alumina crucible, and calcined at 950°C for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain a luminescent temperature fluorescent powder. The obtained luminescent temperature powder is a light red powder, and the molecular formula is 2MgO·Li2O·LiF·LiNb 0.999 Mn 0.001 O3, its emission spectrum under the strongest excitation at 340 nm consists of a broadband emission peak with a peak at 677 nm, and the emission spectrum covers the range of 600-850 nm, as shown in Figure 2 As the temperature rises, the emission peak intensity decreases sharply, as shown in Figure 3 As the temperature rises, the emission peak intensity decreases sharply, as shown in Figure 4 As the temperature rises, the emission peak intensity decreases sharply, as shown in
[0037] Example 5
[0038] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%), and MnO2 (99.99%), and the molar ratio between them is 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 30 minutes, then placed in an alumina crucible, and pre-fired at 650°C for 24 hours. The pre-fired sample is taken out, ground and mixed again, then placed in an alumina crucible, and calcined at 950°C for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain a luminescent temperature fluorescent powder. The obtained luminescent temperature powder is a light red powder, and the molecular formula is 2MgO·Li2O·LiF·LiNb0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, its emission spectrum consists of a broadband emission peak with a peak at 677 nm, the emission spectrum covers the range of 600-850 nm, as shown in Figure 2 ; with the increase of temperature, the emission peak intensity decreases sharply, as shown in Figure 3 ; the emission peak intensity changes linearly with temperature, as shown in Figure 4 ; the best temperature measurement sensitivity of the material in the range of 304K to 460K is 9.34% / K.
[0039] Example 6
[0040] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%) and MnO2 (99.99%), and the molar ratio between them is 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar and ground for about 30 minutes, then put into an alumina crucible, pre-fired at 200℃ for 6 hours. After the pre-fired sample is taken out, it is ground and mixed again, then put into an alumina crucible and calcined at 950℃ for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain luminescent thermometric fluorescent powder. The obtained luminescent thermometric powder is a light red powder, and the molecular formula is 2MgO·Li2O·LiF·LiNb 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, its emission spectrum consists of a broadband emission peak with a peak at 677 nm, the emission spectrum covers the range of 600-850 nm, as shown in Figure 2 ; with the increase of temperature, the emission peak intensity decreases sharply, as shown in Figure 3 ; the emission peak intensity changes linearly with temperature, as shown in Figure 4 ; the best temperature measurement sensitivity of the material in the range of 304K to 460K is 6.71% / K.
[0041] Example 7
[0042] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%) and MnO2 (99.99%) with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar and ground for about 30 minutes, and then placed in an alumina crucible and pre-fired at 800°C for 6 hours. The pre-fired sample is taken out, ground again, mixed uniformly, and then placed in an alumina crucible and calcined at 950°C for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain a luminescence temperature fluorescent powder. The obtained luminescence temperature powder is a light red powder with a molecular formula of 2MgO·Li2O·LiF·LiNbO3. 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, its emission spectrum consists of a broadband emission peak with a peak at 677 nm, and the emission spectrum covers the range of 600-850 nm, as shown in FIG. 2; as the temperature increases, the emission peak intensity decreases sharply, as shown in FIG. 3; the emission peak intensity changes linearly with temperature, as shown in FIG. 4, and the best temperature measurement sensitivity of the material in the range of 304K to 460K is 7.28% / K. Figure 2 Figure 3 Figure 4
[0043] Example 8
[0044] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%) and MnO2 (99.99%) with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar and ground for about 30 minutes, and then placed in an alumina crucible and pre-fired at 650°C for 6 hours. The pre-fired sample is taken out, ground again, mixed uniformly, and then placed in an alumina crucible and calcined at 950°C for 3 hours. After natural cooling, the sample is taken out and carefully ground to obtain a luminescence temperature fluorescent powder. The obtained luminescence temperature powder is a light red powder with a molecular formula of 2MgO·Li2O·LiF·LiNbO3. 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, its emission spectrum consists of a broadband emission peak with a peak at 677 nm, and the emission spectrum covers the range of 600-850 nm, as shown in FIG. 2; as the temperature increases, the emission peak intensity decreases sharply, as shown in FIG. 3; the emission peak intensity changes linearly with temperature, as shown in FIG. 4, and the best temperature measurement sensitivity of the material in the range of 304K to 460K is 7.28% / K. Figure 2 Figure 3 Figure 4
[0045] Example 9
[0046] The raw materials were LiF (99.9%), Li₂CO₃ (99.9%), MgO (99.99%), Nb₂O₅ (99.99%), and MnO₂ (99.99%), with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to this ratio, mixed evenly in an agate mortar, and ground for approximately 30 minutes. The mixture was then placed in an alumina crucible and pre-calcined at 650℃ for 6 hours. The pre-calcined sample was removed, ground and mixed again, and then placed back into the alumina crucible for further calcination at 950℃ for 24 hours. After natural cooling, the sample was removed and carefully ground to obtain the luminescent thermometric phosphor. The obtained luminescent thermometric powder was a light red powder with the molecular formula 2MgO·Li₂O·LiF·LiNb 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, has an emission spectrum consisting of a broadband emission peak at 677 nm, covering the range of 600-850 nm. Figure 2 As shown; with increasing temperature, the emission peak intensity decreases sharply, as... Figure 3 As shown; the emission peak intensity changes linearly with temperature, as... Figure 4 As shown, the optimal temperature sensitivity of the material in the range of 304K to 460K is 9.59% / K.
[0047] Example 10
[0048] The raw materials were LiF (99.9%), Li₂CO₃ (99.9%), MgO (99.99%), Nb₂O₅ (99.99%), and MnO₂ (99.99%), with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to this ratio, mixed evenly in an agate mortar, and ground for approximately 30 minutes. The mixture was then placed in an alumina crucible and pre-calcined at 650℃ for 6 hours. The pre-calcined sample was removed, ground and mixed again, and then placed back into the alumina crucible for further calcination at 800℃ for 6 hours. After natural cooling, the sample was removed and carefully ground to obtain the luminescent thermometric phosphor. The obtained luminescent thermometric powder was a light red powder with the molecular formula 2MgO·Li₂O·LiF·LiNb 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, has an emission spectrum consisting of a broadband emission peak at 677 nm, covering the range of 600-850 nm. Figure 2 As shown; with increasing temperature, the emission peak intensity decreases sharply, as... Figure 3 As shown; the emission peak intensity changes linearly with temperature, as... Figure 4 As shown, the optimal temperature sensitivity of the material in the range of 304K to 460K is 5.31% / K.
[0049] Example 11
[0050] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%) and MnO2 (99.99%) with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar and ground for about 30 minutes, and then placed in an alumina crucible and pre-fired at 650°C for 6 hours. The pre-fired sample is taken out, ground again, mixed uniformly, and then placed in an alumina crucible and calcined at 1100°C for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain a luminescence temperature measuring fluorescent powder. The obtained luminescence temperature measuring powder is a light red powder with a molecular formula of 2MgO·Li2O·LiF·LiNbO3. 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, its emission spectrum consists of a broadband emission peak with a peak at 677 nm, and the emission spectrum covers the range of 600-850 nm, as shown in FIG. 2; as the temperature increases, the emission peak intensity decreases sharply, as shown in FIG. 3; the emission peak intensity changes linearly with temperature, as shown in FIG. 4, and the best temperature measuring sensitivity of the material in the range of 304K to 460K is 6.28% / K. Figure 2 Figure 3 Figure 4
[0051] Example 12
[0052] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%) and MnO2 (99.99%) with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar and ground for about 30 minutes, and then placed in an alumina crucible and pre-fired at 800°C for 24 hours. The pre-fired sample is taken out, ground again, mixed uniformly, and then placed in an alumina crucible and calcined at 1100°C for 24 hours. After natural cooling, the sample is taken out and carefully ground to obtain a luminescence temperature measuring fluorescent powder. The obtained luminescence temperature measuring powder is a light red powder with a molecular formula of 2MgO·Li2O·LiF·LiNbO3. 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, its emission spectrum consists of a broadband emission peak with a peak at 677 nm, and the emission spectrum covers the range of 600-850 nm, as shown in FIG. 2; as the temperature increases, the emission peak intensity decreases sharply, as shown in FIG. 3; the emission peak intensity changes linearly with temperature, as shown in FIG. 4, and the best temperature measuring sensitivity of the material in the range of 304K to 460K is 6.28% / K. Figure 2 Figure 3 Figure 4
[0053] Example 13
[0054] The raw materials were NaF (99.9%), Na2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%), and MnO2 (99.99%) with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 30 minutes before being placed in an alumina crucible and pre-fired at 650°C for 6 hours. After pre-firing, the sample was removed, ground again, mixed uniformly, and placed in an alumina crucible and calcined at 950°C for 6 hours. After natural cooling, the sample was removed and carefully ground to obtain the luminescence temperature measurement phosphor. The obtained luminescence temperature measurement powder was a light red powder with a molecular formula of 2MgO·Na2O·NaF·NaNbO3. The luminescence temperature measurement phosphor was characterized by photoluminescence excitation and emission spectra. 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, its emission spectrum consisted of a broadband emission peak with a peak at 677 nm, and the emission spectrum covered the range of 600-850 nm, as shown in FIG. 2. As the temperature increased, the emission peak intensity decreased sharply, as shown in FIG. 3. The emission peak intensity changed linearly with temperature, as shown in FIG. 4, and the best temperature measurement sensitivity of the material in the range of 304 K to 460 K was 5.57% / K. Figure 2 Figure 3 Figure 4 Example 14
[0055] Example 14
[0056] The raw materials were NaF (99.9%), Na2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%), and MnO2 (99.99%) with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 30 minutes before being placed in an alumina crucible and pre-fired at 200°C for 0.5 hours. After pre-firing, the sample was removed, ground again, mixed uniformly, and placed in an alumina crucible and calcined at 800°C for 3 hours. After natural cooling, the sample was removed and carefully ground to obtain the luminescence temperature measurement phosphor. The obtained luminescence temperature measurement powder was a light red powder with a molecular formula of 2MgO·Na2O·NaF·NaNbO3. The luminescence temperature measurement phosphor was characterized by photoluminescence excitation and emission spectra. 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, its emission spectrum consisted of a broadband emission peak with a peak at 677 nm, and the emission spectrum covered the range of 600-850 nm, as shown in FIG. 2. As the temperature increased, the emission peak intensity decreased sharply, as shown in FIG. 3. The emission peak intensity changed linearly with temperature, as shown in FIG. 4, and the best temperature measurement sensitivity of the material in the range of 304 K to 460 K was 5.57% / K. Figure 2 Figure 3 Figure 4 The emission peak intensity changed linearly with temperature, as shown in FIG. 4, and the best temperature measurement sensitivity of the material in the range of 304 K to 460 K was 2.34% / K.
[0057] Example 15
[0058] The raw materials were NaF (99.9%), Na₂CO₃ (99.9%), MgO (99.99%), Nb₂O₅ (99.99%), and MnO₂ (99.99%), with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to this ratio, mixed evenly in an agate mortar, and ground for approximately 30 minutes. The mixture was then placed in an alumina crucible and pre-calcined at 800℃ for 24 hours. The pre-calcined sample was removed, ground and mixed again, and then placed back into the alumina crucible for further calcination at 1100℃ for 24 hours. After natural cooling, the sample was removed and carefully ground to obtain the luminescent thermometric phosphor. The obtained luminescent thermometric powder was a light red powder with the molecular formula 2MgO·Na₂O·NaF·NaNb 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, has an emission spectrum consisting of a broadband emission peak at 677 nm, covering the range of 600-850 nm. Figure 2 As shown; with increasing temperature, the emission peak intensity decreases sharply, as... Figure 3 As shown; the emission peak intensity changes linearly with temperature, as... Figure 4 As shown, the optimal temperature sensitivity of the material in the range of 304K to 460K is 5.65% / K.
[0059] Example 16
[0060] The raw materials were KF (99.9%), K₂CO₃ (99.9%), MgO (99.99%), Nb₂O₅ (99.99%), and MnO₂ (99.99%), with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to this ratio, mixed evenly in an agate mortar, and ground for approximately 30 minutes. The mixture was then placed in an alumina crucible and pre-calcined at 650℃ for 6 hours. The pre-calcined sample was removed, ground and mixed again, and then placed back into the alumina crucible for further calcination at 950℃ for 6 hours. After natural cooling, the sample was removed and carefully ground to obtain the luminescent thermometric phosphor. The obtained luminescent thermometric powder was a light red powder with the molecular formula 2MgO·K₂O·KF·KNb. 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, has an emission spectrum consisting of a broadband emission peak at 677 nm, covering the range of 600-850 nm. Figure 2 As shown; with increasing temperature, the emission peak intensity decreases sharply, as... Figure 3 As shown; the emission peak intensity changes linearly with temperature, as... Figure 4As shown, the optimal temperature sensitivity of the material in the range of 304K to 460K is 7.82% / K.
[0061] Example 17
[0062] The raw materials were KF (99.9%), K₂CO₃ (99.9%), MgO (99.99%), Nb₂O₅ (99.99%), and MnO₂ (99.99%), with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to this ratio, mixed evenly in an agate mortar, and ground for approximately 30 minutes. The mixture was then placed in an alumina crucible and pre-calcined at 800℃ for 24 hours. The pre-calcined sample was removed, ground and mixed again, and then placed back into the alumina crucible for further calcination at 1100℃ for 24 hours. After natural cooling, the sample was removed and carefully ground to obtain the luminescent thermometric phosphor. The obtained luminescent thermometric powder was a light red powder with the molecular formula 2MgO·K₂O·KF·KNb. 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, has an emission spectrum consisting of a broadband emission peak at 677 nm, covering the range of 600-850 nm. Figure 2 As shown; with increasing temperature, the emission peak intensity decreases sharply, as... Figure 3 As shown; the emission peak intensity changes linearly with temperature, as... Figure 4 As shown, the optimal temperature sensitivity of the material in the range of 304K to 460K is 5.96% / K.
[0063] Example 18
[0064] The raw materials were LiF (99.9%), Li₂CO₃ (99.9%), ZnO (99.99%), Nb₂O₅ (99.99%), and MnO₂ (99.99%), with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to this ratio, mixed evenly in an agate mortar, and ground for approximately 30 minutes. The mixture was then placed in an alumina crucible and pre-calcined at 650℃ for 6 hours. The pre-calcined sample was removed, ground and mixed again, and then placed back into the alumina crucible for further calcination at 950℃ for 6 hours. After natural cooling, the sample was removed and carefully ground to obtain the luminescent thermometric phosphor. The obtained luminescent thermometric powder was a light red powder with the molecular formula 2ZnO·Li₂O·LiF·LiNb. 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, has an emission spectrum consisting of a broadband emission peak at 677 nm, covering the range of 600-850 nm. Figure 2 As shown; with increasing temperature, the emission peak intensity decreases sharply, as... Figure 3 As shown; the emission peak intensity changes linearly with temperature, as...Figure 4 The best temperature measurement sensitivity of the material is 8.54% / K in the range of 304K to 460K, as shown in FIG. 6.
[0065] Example 19
[0066] The raw materials were LiF (99.9%), Li2CO3 (99.9%), ZnO (99.99%), Nb2O5 (99.99%), and MnO2 (99.99%) with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 30 minutes, and then placed in an alumina crucible and pre-fired at 800°C for 24 hours. The pre-fired sample was taken out, ground again, mixed uniformly, and then placed in an alumina crucible and calcined at 1100°C for 24 hours. After natural cooling, the sample was taken out and carefully ground to obtain a luminescent temperature fluorescent powder. The obtained luminescent temperature powder was a light red powder with a molecular formula of 2ZnO·Li2O·LiF·LiNbO3. 0.999 Mn 0.001 The emission spectrum of the material under the strongest excitation at 340 nm consists of a broadband emission peak with a peak at 677 nm, and the emission spectrum covers the range of 600-850 nm, as shown in FIG. 5. As the temperature increases, the emission peak intensity decreases sharply, as shown in FIG. 6. The emission peak intensity changes linearly with temperature, as shown in FIG. 7. The best temperature measurement sensitivity of the material is 6.21% / K in the range of 304K to 460K. Figure 2 Figure 3 Figure 4 The best temperature measurement sensitivity of the material is 8.54% / K in the range of 304K to 460K, as shown in FIG. 6.
[0067] Example 20
[0068] The raw materials were LiF (99.9%), Li2CO3 (99.9%), CaCO3 (99.99%), Nb2O5 (99.99%), and MnO2 (99.99%) with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 30 minutes, and then placed in an alumina crucible and pre-fired at 800°C for 24 hours. The pre-fired sample was taken out, ground again, mixed uniformly, and then placed in an alumina crucible and calcined at 1100°C for 24 hours. After natural cooling, the sample was taken out and carefully ground to obtain a luminescent temperature fluorescent powder. The obtained luminescent temperature powder was a light red powder with a molecular formula of 2ZnO·Li2O·LiF·LiNbO3. 0.999 Mn 0.001 The emission spectrum of the material under the strongest excitation at 340 nm consists of a broadband emission peak with a peak at 677 nm, and the emission spectrum covers the range of 600-850 nm, as shown in FIG. 5. As the temperature increases, the emission peak intensity decreases sharply, as shown in FIG. 6. The emission peak intensity changes linearly with temperature, as shown in FIG. 7. The best temperature measurement sensitivity of the material is 6.21% / K in the range of 304K to 460K. Figure 2 Figure 3 The emission peak intensity varies linearly with temperature, as shown in Figure 4 The optimum temperature-sensing sensitivity of the material is 6.24% / K in the range of 304K to 460K, as shown in
[0069] Example 21
[0070] The raw materials were LiF (99.9%), Li2CO3 (99.9%), CaCO3 (99.99%), Nb2O5 (99.99%), and MnO2 (99.99%), with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 30 minutes before being placed in an alumina crucible and pre-fired at 800°C for 24 hours. The pre-fired sample was removed, ground again, mixed uniformly, and placed in an alumina crucible and calcined at 1100°C for 24 hours. After natural cooling, the sample was removed and carefully ground to obtain the luminescent temperature fluorescent powder. The obtained luminescent temperature powder was a light red powder with a molecular formula of 2CaO·Li2O·LiF·LiNbO3. 0.999 Mn 0.001 The emission spectrum of the material under the strongest excitation at 340nm consists of a broadband emission peak with a peak value at 677nm, and the emission spectrum covers the range of 600-850nm, as shown in Figure 2 As the temperature increases, the emission peak intensity decreases sharply, as shown in Figure 3 The emission peak intensity varies linearly with temperature, as shown in Figure 4 The optimum temperature-sensing sensitivity of the material is 4.31% / K in the range of 304K to 460K, as shown in
[0071] Example 22
[0072] The raw materials were LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Sb2O5 (99.99%), and MnO2 (99.99%), with a molar ratio of 1:1.5:2:0.4995:0.001. The raw materials were weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 30 minutes before being placed in an alumina crucible and pre-fired at 650°C for 6 hours. The pre-fired sample was removed, ground again, mixed uniformly, and placed in an alumina crucible and calcined at 950°C for 6 hours. After natural cooling, the sample was removed and carefully ground to obtain the luminescent temperature fluorescent powder. The obtained luminescent temperature powder was a light red powder with a molecular formula of 2MgO·Li2O·LiF·LiSbO3. 0.999 Mn 0.001 The emission spectrum of the material under the strongest excitation at 340nm consists of a broadband emission peak with a peak value at 677nm, and the emission spectrum covers the range of 600-850nm, as shown in Figure 2The emission peak intensity decreases sharply with the increase of temperature, as shown in Figure 3 The emission peak intensity changes linearly with temperature, as shown in Figure 4 The optimum temperature sensing sensitivity of the material is 8.45% / K in the range of 304K to 460K.
[0073] Example 23
[0074] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Sb2O5 (99.99%), and MnO2 (99.99%), and the molar ratio between them is 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 30 minutes before being placed in an alumina crucible and pre-fired at 800°C for 24 hours. The pre-fired sample is taken out, ground and mixed again, and then placed in an alumina crucible and calcined at 1100°C for 24 hours. After natural cooling, the sample is taken out and carefully ground to obtain the luminescent temperature fluorescent powder. The obtained luminescent temperature powder is a light red powder, and the molecular formula is 2MgO·Li2O·LiF·LiSb 0.999 Mn 0.001 O3, and its emission spectrum consists of a broadband emission peak with a peak at 677nm under the strongest excitation at 340nm, covering the range of 600-850nm, as shown in Figure 2 The emission peak intensity decreases sharply with the increase of temperature, as shown in Figure 3 The emission peak intensity changes linearly with temperature, as shown in Figure 4 The optimum temperature sensing sensitivity of the material is 5.36% / K in the range of 304K to 460K.
[0075] Example 24
[0076] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%), and MnO2 (99.99%), and the molar ratio between them is 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 5 minutes before being placed in an alumina crucible and pre-fired at 650°C for 6 hours. The pre-fired sample is taken out, ground and mixed again, and then placed in an alumina crucible and calcined at 950°C for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain the luminescent temperature fluorescent powder. The obtained luminescent temperature powder is a light red powder, and the molecular formula is 2MgO·Li2O·LiF·LiNb 0.999 Mn 0.001O3, its emission spectrum consists of a broadband emission peak with a peak at 677 nm under the strongest excitation at 340 nm, and the emission spectrum covers the range of 600-850 nm, as shown in Figure 2 With the increase of temperature, the emission peak intensity decreases sharply, as shown in Figure 3 The emission peak intensity changes linearly with temperature, as shown in Figure 4 The best temperature measurement sensitivity of the material in the range of 304K to 460K is 7.51% / K.
[0077] Example 25
[0078] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%), and MnO2 (99.99%), and the molar ratio between them is 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 120 minutes, then placed in an alumina crucible, and pre-fired at 650°C for 6 hours. The pre-fired sample is taken out, ground again, mixed uniformly, and placed in an alumina crucible, and calcined at 950°C for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain a luminescent thermometric fluorescent powder. The obtained luminescent thermometric powder is a light red powder, and the molecular formula is 2MgO·Li2O·LiF·LiNb 0.999 Mn 0.001 O3, its emission spectrum consists of a broadband emission peak with a peak at 677 nm under the strongest excitation at 340 nm, and the emission spectrum covers the range of 600-850 nm, as shown in Figure 2 With the increase of temperature, the emission peak intensity decreases sharply, as shown in Figure 3 The emission peak intensity changes linearly with temperature, as shown in Figure 4 The best temperature measurement sensitivity of the material in the range of 304K to 460K is 9.62% / K.
[0079] Example 26
[0080] The raw materials are LiF (99.9%), Li2CO3 (99.9%), MgO (99.99%), Nb2O5 (99.99%), and MnO2 (99.99%), and the molar ratio between them is 1:1.5:2:0.4995:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 120 minutes, then placed in an alumina crucible, and pre-fired at 650°C for 6 hours. The pre-fired sample is taken out, ground again, mixed uniformly, and placed in an alumina crucible, and calcined at 950°C for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain a luminescent thermometric fluorescent powder. The obtained luminescent thermometric powder is a light red powder, and the molecular formula is 2MgO·Li2O·LiF·LiNb0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, its emission spectrum consists of a broadband emission peak with a peak at 677 nm, the emission spectrum covers the range of 600-850 nm, as shown in Figure 2 ; with the increase of temperature, the emission peak intensity decreases sharply, as shown in Figure 3 ; the emission peak intensity changes linearly with temperature, as shown in Figure 4 ; the best temperature measurement sensitivity of the material in the range of 304K to 460K is 7.85% / K.
[0081] Example 27
[0082] The raw materials are LiF (99.9%), CH3COOLi (99.9%), Mg (CH3COO) 2 (99.99%), Nb (CH3COO) 5 (99.99%) and Mn (CH3COO) 4 (99.99%), and the molar ratio between them is 1:3:2:0.999:0.001. The raw materials are weighed according to the above ratio, mixed uniformly in an agate mortar, and ground for about 30 minutes, then put into an alumina crucible, and pre-fired at 650℃ for 6 hours. The pre-fired sample is taken out, ground and mixed again, then put into an alumina crucible, and calcined at 950℃ for 6 hours. After natural cooling, the sample is taken out and carefully ground to obtain a luminescent temperature fluorescent powder. The obtained luminescent temperature powder is a light red powder, and the molecular formula is 2MgO·Li2O·LiF·LiNb 0.999 Mn 0.001 O3, under the strongest excitation at 340 nm, its emission spectrum consists of a broadband emission peak with a peak at 677 nm, the emission spectrum covers the range of 600-850 nm, as shown in Figure 2 ; with the increase of temperature, the emission peak intensity decreases sharply, as shown in Figure 3 ; the emission peak intensity changes linearly with temperature, as shown in Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 Figure 3 Figure 4 Figure 2 ; the best temperature measurement sensitivity of the material in the range of 304K to 460K is 8.79% / K.
[0083] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A highly sensitive fluorescent thermometric material, characterized in that, Fluorescent thermometric materials have the following general formula: A4B2M 1-x O6F:xMn 4+ , Wherein, metal A is one or more of elements Na, Li, and K; metal B is one or more of elements Mg, Zn, and Ca; metal M is one or both of elements Nb and Sb; and Mn... 4+ The doping amount x ranges from 0.05 mol% to x ≤ 1 mol%.
2. The highly sensitive fluorescent thermometric material according to claim 1, characterized in that, The fluorescent thermometric material has a face-centered cubic rock salt structure and can be excited by near-ultraviolet or visible light of 300-600nm, emitting red light in the range of 600-850nm.
3. A method for preparing a highly sensitive fluorescent thermometric material, used to prepare the highly sensitive fluorescent thermometric material as described in any one of claims 1-2, characterized in that, Includes the following steps: (1) The manganese source, the source containing metal A, the source containing metal B and the source containing metal M are thoroughly mixed and ground once to obtain a raw material mixture; wherein the source containing metal A is a combination of fluoride of metal A and carbonate of metal A, and the molar ratio of fluoride of metal A to carbonate of metal A is 1:1.5; or any one of the combination of fluoride of metal A and nitrate of metal A, or combination of fluoride of metal A and acetate of metal A, and the molar ratio of fluoride of metal A to nitrate of metal A is 1:3, and the molar ratio of fluoride of metal A to acetate of metal A is 1:3; The molar ratio of fluorides in the B-metal source to those in the A-metal source is 2:1; The molar ratio of the M-containing metal source to the manganese source is (0.99-0.9995):(0.0005-0.01); (2) The raw material mixture is pre-calcined at 200-800℃ for 0.5-24 hours, cooled to room temperature, and then ground twice to obtain a pre-calcined mixture; (3) The pre-calcined mixture is sintered at 800-1100℃ for 3-24 hours. After cooling, the sample is taken out and ground three times to obtain the fluorescent thermometric material.
4. The method for preparing a highly sensitive fluorescent thermometric material according to claim 3, characterized in that, The manganese source includes any one or more combinations of manganese-containing oxides, carbonates, halides, oxalates, acetates, or nitrates; the A-containing metal source includes any one or more combinations of A-containing oxides, halides, carbonates, nitrates, oxalates, citrates, or acetic acid; the B-containing metal source includes any one or more combinations of B-containing oxides, halides, carbonates, oxalates, citrates, acetates, or acetic acid; and the M-containing metal source includes any one or more combinations of M-containing oxides, carbonates, nitrates, oxalates, citrates, or acetic acid.
5. The method for preparing a highly sensitive fluorescent thermometric material according to claim 3, characterized in that, When metal A is Li, the metal source corresponding to metal A is a combination of LiF and Li2CO3, LiF and LiNO3, or LiF and CH3COOLi; when metal A is Na, the metal source corresponding to metal A is a combination of NaF and Na2CO3; when metal A is K, the metal source corresponding to metal A is a combination of KF and K2CO3.
6. The method for preparing a highly sensitive fluorescent thermometric material according to claim 3, characterized in that, When metal B is Mg, the corresponding metal source for metal B is MgO, Mg(NO3)2 or Mg(CH3COO)2; when metal B is Zn, the corresponding metal source for metal B is ZnO; when metal B is Ca, the corresponding metal source for metal B is CaCO3.
7. The method for preparing a highly sensitive fluorescent thermometric material according to claim 3, characterized in that, When M is Nb, the corresponding metal source is Nb2O5, Nb(NO3)5, or Nb(CH3COO)5; when M is Sb, the corresponding metal source is Sb2O5; when M is Ta, the corresponding metal source is Ta2O5; when M is P, the corresponding metal source is P2O5; when M is V, the corresponding metal source is V2O5; and when M is Ta, P, or V, the molar ratio of its corresponding metal source to Nb2O5 is (0.005-0.25):(0.4995-0.25).
8. The method for preparing a highly sensitive fluorescent thermometric material according to claim 3, characterized in that... The time for the first, second, and third grinding processes is 5-120 minutes.